Mass Production Media of Biofertilizer N Fixer Azotobacter sp. from Rhizosphere in Indonesia - Nicky O Fauziah; Nida N Rusdiyono; Tualar Simarmata; Betty N Fitriatin (JURNAL BUDIDAYA PERTANIAN, 2022)
Mass production media of biofertilizer must be able to maintain the shelf-life in accordance with provisions of the Regulation of the Minister of Agriculture Number 01 of 2019 concerning Organic Fertilizer, Biofertilizer, and Ameliorant. This paper review aims to provide an overview of the media of mass production Azotobacter biofertilizer in Indonesia. Azotobacter biofertilizer in the form of a single liquid or solid fertilizer must have a minimum population of 1x108 CFU/g. Isolation of the nitrogen fixer microbe Azotobacter can be carried out through one or more agroecosystems, after that grown at selective media, pick the carrier either liquid or solid carrier, and additive that can increase microbial viability. Liquid carriers have more advantages over solid carriers. Before commercializing, it is necessary to check the quality of the biofertilizer referring to applicable regulations.